Tělocvičný spolek paní a dívek pražských - Štěpánová, Irena (Lidé města, 2003)
The presented study examines the history of the Physical Education Association of Prague Ladies unci Girls. The organisation was established in 1869, six years after the establishment of men's Sokol as the first ever association of this type. From the very beginning, it was headed by prominent writers and wives of outstanding personalities. The association was not only a sports club, but an organisation with a strong Czech national focus. At the same time, from the beginning it tried to advocate equal position of women in education and social life. It fostered active contacts with other women's organisations, the Ladies' American Club and the Women's Czech Production Association (the same women actively worked at the same time in all of these associations). However, relationships with the men's Sokol were the most important ones. The association depended on the lease of its gym, it was organised along its lines, it used the same phraseology and there was also a large number of personal, friendly and family contacts. Since the early 1890s, when the "women's question" started to become an urgent issue and when circles of training women started to be established in the countryside en masse, the leadership of Sokol felt compelled to settle their incorporation and statute within the organisation. But this development was very slow. In fact, the question was only resolved in the years after World War One. In this process women's associations had to conquer a more equal position step by step. They were considered just as "minor ones". They had to pay full membership fees, while they had no voting right. The Physical Education Association of Prague Ladies only took part in this since 1909. At that time the Association was in the grip of a deep crisis, along with a conflict of generations. Older members defended their existent, relatively independent emancipated position within Sokol, they wanted to be included in the organisation as other women's associations and along with them sought gradual emancipation. After a replacement at the leading positions in 1912, the association became the Women's Branch of the Prague Sokol. With this name, it took part in the Sokol Vlth national festival in June 1912. The "women's question" in Sokol was only resolved in the inter-war period.